The Study of The Factor Structure of The Thai Version of Geloph <15> - Virangkur, Damisa; Chantagul, Natalie (Scholar: Human Sciences, 2016)
The present study was designed to investigate the factor structure of the Thai version of the GELOPH<15> scale in Thailand and test its reliability and validity via its relationship with measures of self-esteem and life satisfaction. The participants consisted of 210 Thai citizens (58 males, 152 females) aged over 18 years and willing to fill in the study’s questionnaire. Exploratory factor analysis of the Thai version of GELOPH<15> yielded three factors (i.e., inability to deal with gelotophobia, negative reaction towards gelotophobia, and social avoidance) that are different from the original GELOPH<15> German version in which one dimension fit its data best and was identified by Ruch and Proyer (2008). Test of convergent validity showed that the GELOPH<15>’s three factors have negative correlation with self-esteem and life satisfaction. The analysis of demographic differences revealed that gender, age, and marital status have no significant effect on the three gelotophobia factors.